Information Seeking Pattern Relating to Football (A Case Study of Information Seeking of Football News As a Result of Unpublished Soccer Tabloid) - Mabchut Nahdi, Faris; Noor Rakhmad, M.I.Kom, Drs. Wiwid (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
Soccer Tabloid is a football media that stopped its publishing in October, 2014. Based on the data of Kominfo and APJII, the unpublished Soccer Tabloid was concured with the increasing consumption of online media in Indonesia. Soccer Tabloid stopped its production due to the declining of selling circulation per year. As a result of the failed production of Soccer Tabloid, the readers are forced to seek the information from other media The purpose of this study is to describe the orientation of information seeking pattern perpetrated by the Soccer Tabloid readers after failing in production since 2014. This research uses Descriptive Case Study Approach along with Post-Positivist Paradigm. It also applies Information Seeking Theory and Uses and Gratification Theory. The technique of data analysis in this study requires the analytic technique of pattern-matching by Robert K. Yin. This study acknowledges the result that matches with the predicted pattern in which the information seeking pattern alteration is solely addressed to certain age categories. It can be seen from the research subjects with age category of 18 to 25 and age category of 26 to 35, they switch to use online media in fulfilling their information needs, contrasting with age category of 36 to 45 who still uses mass media In conclusion, information understanding recognized by each informant relating to football news from the media they consume results in activity, namely media preference in fulfilling information needs about football. The motives of each informant are various as well in consuming Socccer Tabloid due to their own needs. After Soccer Tabloid bankruptcy, informants apply the broad and narrow strategy selections in media preference to fulfill the needs of football information.